Scientific Activity: A Critical Perspective from Psychological Referents - Villarruel-Fuentes, Manuel (2019)
Science as organized thought is subject to rules and principles that are embodied in the daily practice of the subject who thinks and does research. Aligned with this, it is possible to identify irrational behaviors called cognitive biases, which affect the outcome of any process of inquiry and generation of knowledge. Based on this, a critical analysis is presented on those biases that affect the thinking of the scientist who makes and teaches science, in search of conceptual approaches that support new research problems.